Comparing Patterns of Hurricane Washover into Built and Unbuilt Environments. Issue 3 (9th March 2021) - Lazarus, Eli D.; Goldstein, Evan B.; Taylor, Luke A.; Williams, Hannah E.
Abstract: Extreme geohazard events can change landscape morphology by redistributing huge volumes of sediment. Event‐driven sediment deposition is typically studied in unbuilt settings – despite the ubiquity of occurrence and high economic cost of these geohazard impacts in built environments. Moreover, sedimentary consequences of extreme events in built settings tend to go unrecorded because they are rapidly cleared, at significant expense, from streets and roads to facilitate emergency response. Reducing disaster costs requires an ability to predict disaster impacts, which itself requires comprehensive measurement and study of the physical consequences of geohazard events. Here, using a database of poststorm aerial imagery, we measure plan‐view geometric characteristics of sandy washover deposits in built and unbuilt settings following five different hurricane strikes along the Atlantic and Gulf Coasts of the US since 2011. We identify systematic similarities and differences between washover morphology in built and unbuilt environments, which we further explore with a simplified numerical model. Our findings suggest that spatial characteristics of the built environment (termed "fabric") – specifically, the built fraction of the depositional zone – exerts a fundamental control on the form of large deposits. Accounting for the influence of built fabric on the morphodynamics of flow‐driven geohazards is a tractable step toward improved forecasts of hazard impacts and disaster risk reduction. Plain‐language Summary: Many kinds of hazardous extreme events – floods, landslides, and volcanic activity – send flows laden with sediment coursing into built environments. For example, when hurricanes strike built‐up areas of low‐lying coastline, huge volumes of sand get channeled down streets and between buildings, requiring expensive emergency clean‐up. Patterns of hurricane‐driven deposition in the fabric of built settings have been described but rarely measured. We measure hurricane deposits in built and unbuilt environments and find systematic similarities and differences between the two types of setting. Our findings suggest that assessment and mitigation of disaster risk in built environments prone to flow‐driven hazards could be improved by accounting for the effect of built fabric on sediment dynamics. Key Points: We measure geometric characteristics of sandy washover deposits in built and unbuilt coastal environments following hurricane strikes We quantify systematic similarities and differences between washover morphology in built and unbuilt environments Our findings suggest that the "fabric" of the built environment exerts a fundamental control on large washover deposit form